2006
DOI: 10.1016/j.ydbio.2005.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Brg1 is required for murine neural stem cell maintenance and gliogenesis

Abstract: Epigenetic alterations in cell-type-specific gene expression control the transition of neural stem cells (NSCs) from predominantly neurogenic to predominantly gliogenic phases of differentiation, but how this switch occurs is unclear. Here, we show that brahma-related gene 1 (Brg1), an ATP-dependent chromatin remodeling factor, is required for the repression of neuronal commitment and the maintenance of NSCs in a state that permits them to respond to gliogenic signals. Loss of Brg1 in NSCs in conditional brg1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
125
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 35 publications
15
125
0
Order By: Relevance
“…In nonamniotic vertebrates, like frogs and fish, Brg1 has been observed to promote differentiation rather than the maintenance of stem cells/progenitors (29,30). A more recent study, using the conditional knock-out strategy, has reaffirmed the earlier observations that Brg1 maintains stem cells, whereas Brm promotes their differentiation in mammals (31). Our study demonstrates a similar role for Brm in retinal progenitors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In nonamniotic vertebrates, like frogs and fish, Brg1 has been observed to promote differentiation rather than the maintenance of stem cells/progenitors (29,30). A more recent study, using the conditional knock-out strategy, has reaffirmed the earlier observations that Brg1 maintains stem cells, whereas Brm promotes their differentiation in mammals (31). Our study demonstrates a similar role for Brm in retinal progenitors.…”
Section: Discussionsupporting
confidence: 82%
“…For example, these complexes have been shown to facilitate the differentiation of a variety of cell types such as erythrocytes (7,23), macrophages (24), myeloid cells (25), adipocytes (26), myoblasts (27), osteoblasts (28), neurons (29,30), and glia (31). Here we demonstrate the role of Brm in the differentiation of retinal progenitors into RGCs.…”
mentioning
confidence: 55%
“…The role of SWI/SNF by all indications is far reaching. In mammals it is involved in many developmental programs such as muscle [19][20][21][22], heart [23], blood [24], skeletal [25], neuron [26][27][28][29], adipocyte [30], liver [31] and immune system/Tcell development [32,33]. Yeast SWI/SNF has been shown to be involved in an early step in homologous recombination (HR) while RSC promotes HR at the stage of strand invasion [34,35].…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%
“…For example, Matsumoto et al (2006) showed that BRG1 is required for murine neural stem cell maintenance and gliogenesis. No data were found on the function of BRG1 in the biology of mesenchymal stem cells (MSCs), which have a key role in the body's homeostasis.…”
Section: Introductionmentioning
confidence: 99%